THE EXISTENCE OF “SAPI/PISANG” PEOPLE: CHALLENGES AND OPPORTUNITIES FOR INDONESIA-PHILIPPINES BORDER AREA DEVELOPMENT - Sandy Nur Ikfal Raharjo; Ganewati Wuryandari (Jurnal Kajian Wilayah, 2019)
Indonesia’s border region to Phillippines,  especially to the Sangihe Islands which borders to southern, is mostly a less developed area. To accelerate development of this border region, Indonesia and the Philippines need to exercise a strategy  which optimize social connectivity which has been existed  since centuries by the Indonesian Sangihe people known as Sangir-Philippines (“Sapi”) or the Philippines-Sangir (“Pisang”). Although they are sovereign states now with their sovereign territorial rights, these facts  do not prevent these peoples to continue their traditional cross border for the purpose of social, culture and economic activities. This paper examines how their social connectivity could be utilized to develop border area between Indonesia and the Philippine. By using qualitative methods, the data for this paper is collected  from interviews, focus group discussions, field research and literature reviews.This paper concludes that social connectivity among Sapi/Pisang people on the Indonesian and the Philippines respective side raises some challenges such as problems of stateless people, illegal cross-border activities, and terrorism-related activities. However, this paper also found out some positive impacts from their social connectivities, such as  the establishment of traditional cross-border cooperation and trade, the opening of the Davao-Bitung ferry line, and cooperation between regional governments. As a step forward, this research emphasizes the importance of strong political will and active participation from both countries in utilizing social connectivity to build a shared border region.Keywords: “Sapi”, “Pisang”, Border, Social Connectivity, Development, Indonesia, Philippine AbstrakKawasan Perbatasan Indonesia di Kepulauan Sangihe yang berbatasan dengan Filipina bagian selatan, tergolong sebagai daerah tertinggal. Untuk mempercepat pembangunan kawasan tersebut, Indonesia dan Filipina dapat melaksanakan strategi yang memanfaatkan konektivitas sosial yang sudah dibangun oleh masyarakat perbatasan yang dikenal dengan istilah Sangir-Philipina (Sapi) atau Philipina-Sangir (Pisang). Berdirinya Indonesia dan Filipina sebagai dua negara yang berdaulat sejak berakhirnya Perang Dunia II ternyata tidak menghentikan orang Sapi/Pisang untuk melakukan kegiatan lintas batas tradisional untuk tujuan sosial, budaya, dan ekonomi. Tulisan ini menganalisis bagaimana dampak negatif dan dampak positif dari konektivitas sosial di atas dalam membangun kawasan perbatasan Indonesia-Filipina. Dengan menggunakan pendekatan kualitatif, pengumpulan data dilakukan melalui wawancara, diskusi kelompok terpimpin, penelitian lapangan dan studi pustaka. Tulisan ini menyimpulkan bahwa konektivitas sosial antar orang-orang Sapi/Pisang di sisi Indonesia dan di sisi Filipina menimbulkan masalah berupa orang-orang tanpa kewarganegaraan, kegiatan lintas batas ilegal, dan aktivitas terkait terorisme. Namun demikian, Tulisan ini juga menemukan dampak positif dari konektivitas sosial di atas berupa terjalinnya kerja sama lintas batas tradisional dan perdagangan, pembukaan jalur kapal feri Davao-Bitung, dan kerja sama antar pemerintah daerah. Sebagai langkah ke depan, penelitian ini menekankan pentingnya kehendak politik yang kuat dan partisipasi aktif dari kedua negara dalam memanfaatkan konektivitas sosial untuk membangun kawasan perbatasan bersama.